2016
DOI: 10.1186/s12995-016-0116-7
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviour, health status and occupational prospects of apprentice nurses and kindergarten teachers in Germany: a cross-sectional study

Abstract: BackgroundApprentices in human service professions are exposed to emotional and physical stresses in their workplaces. Moreover, they are in the vulnerable phase of becoming an adult. Their lifestyle and health therefore seem to be particularly unstable. This study aims to evaluate and compare the health behaviour, health status and occupational prospects of apprentices in nursing and early childhood education and to identify factors associated with their physical and mental health.MethodsA cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
2
20
0
3
Order By: Relevance
“…In the current study, a significant correlation was observed between the education level and health knowledge, which is in line with the studies conducted by Yaghobian et al and Wirth et al, which revealed that those who have a higher level of education, had broader knowledge about health as well. 18,19 Regarding the correlation between marital status, health knowledge and awareness of patient's rights, married people had higher levels of such knowledge compared to single people, which is in line with research conducted by Yuan et al 20 One possible explanation of this is that couples share their knowledge and spend time together discussing health-related issues.…”
Section: Discussionsupporting
confidence: 79%
“…In the current study, a significant correlation was observed between the education level and health knowledge, which is in line with the studies conducted by Yaghobian et al and Wirth et al, which revealed that those who have a higher level of education, had broader knowledge about health as well. 18,19 Regarding the correlation between marital status, health knowledge and awareness of patient's rights, married people had higher levels of such knowledge compared to single people, which is in line with research conducted by Yuan et al 20 One possible explanation of this is that couples share their knowledge and spend time together discussing health-related issues.…”
Section: Discussionsupporting
confidence: 79%
“…For example, apprentices in the craft and industry sector displayed higher activity levels than those in service and trade sectors and those with a predominantly sedentary job [29]. Importantly, nursing apprentices in hospitals tend to be more engaged with PA than apprentices in early childhood education [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings show that overweight people were more likely to have health problems [ 24 ]. The occupational social environmental factors, such as usual work in bent and twisted postures, less physical activities, high screen time activities, skipping breakfast, and continuous exposure to a high level of noise, are associated with unhealthy behaviors [ 17 , 35 , 36 ]. In our study, overweight teachers had the highest nutrition knowledge among the three grades of BMI, which suggests that these participants had certain but insufficient knowledge of nutrition to change their unhealthy lifestyles.…”
Section: Discussionmentioning
confidence: 99%